TECHNOLOGY OF CONSTRUCTION OF PATHS AND PLAYGROUNDS IN PARKS - Ubaydullaev Farkhod Bakhtiyarullaevich; Xudoyberdiyeva Nargiza Turğunbayevna (Journals Park Publishing, 2025)
This work discusses modern technologies and methods for the construction of paths and playgrounds in parks. The article covers the main stages of the construction process, such as marking the paths and playgrounds, preparing the base, selecting materials, establishing the profile, and working with high-quality concrete or paving tiles. Additionally, the factors that should be considered when constructing paths under different soil conditions and the careful selection of materials are discussed. The construction technologies used for paths and playgrounds in parks help create a stable and aesthetically pleasing environment for people.
Keywords: Parks, path construction, playground construction, construction technologies, base preparation, paving tiles, geotextile, drainage system, profile laying, concrete coating, dry mix, material selection, quality construction, stable environment, aesthetic appearance.